2013
DOI: 10.1097/brs.0b013e31828f494c
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Outcomes and Complications of Anterior and Posterior Cervical Fusion With Bone Morphogenetic Protein

Abstract: Our study found that "off-label" use of BMP as an adjunct to cervical fusions was associated with increased rates of dysphagia in ACFs and increased costs for all cervical fusions. Our study does not measure long-term outcomes after discharge; however, the impact of increased inhospital costs, length of stay, and incidence of dysphagia with utilization of BMP should be considered prior to its use in cervical fusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 19 publications
2
49
0
Order By: Relevance
“…The overall complication rate of cervical spinal surgery is estimated to be 0.2% to 17.8%. 4,17,27,48 After 30 days, the most common complication is related to instrumentation dislodgement, breakage, or both, and occurs in 2% to 25% of cases of spinal fusion procedures. 27 Reoperation rate for instrumented spinal fusions is reported between 2% and 25%, with the majority related to pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The overall complication rate of cervical spinal surgery is estimated to be 0.2% to 17.8%. 4,17,27,48 After 30 days, the most common complication is related to instrumentation dislodgement, breakage, or both, and occurs in 2% to 25% of cases of spinal fusion procedures. 27 Reoperation rate for instrumented spinal fusions is reported between 2% and 25%, with the majority related to pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is a well-known complication after anterior surgeries [73]. Multilevel surgery and bone morphogenetic protein have been raised as risk factors [74,75]. Newer low profile implants and perioperative steroid administration were shown to be effective in reducing dysphagia by reducing retropharyngeal edema [76,77].…”
Section: Complicationsmentioning
confidence: 99%
“…To note, hospital charges only indirectly correlate with the expenditure health-care related resources and hospital collections. During a comparable time period, Fineberg et al [20] found BMP use was associated with increased costs for all cervical fusions. On average, there was a $5092 and $6272 increase in hospital costs for ACFs and PCFs, respectively.…”
Section: Costmentioning
confidence: 99%
“…Given the ongoing uncertainty with the risks and benefits of using BMP in certain off-label applications, various groups have studied the utilization and cost impacts of BMP on a national scale before and after the FDA warnings [2,4,16,20,26,27]. Although the recommended guidelines for limited BMP utilization in spinal fusions have not changed, the rate and type of procedures with BMP continue to increase.…”
Section: Introductionmentioning
confidence: 99%